THE EFFECT OF BRAND REPUTATION, PRODUCT RELIABILITY, PRICE AND BRAND ADMIRATION ON PURCHASING DECISION (Study on Food Products that Sold through Instagram at Semarang) - Mariska, Angela; Soesanto, Harry; Mahfudz, Mahfudz (Master of Management Diponegoro University, 2018)
Development in technology was really fast, especially in the information and telecommunications field. Nowadays, technology cannot be replaced by human life. Social media is very important to various business and personal life. Social media helping us to find new colleagues and help us to easier get information. For many years, most powerful social media are Facebook, Twitter, and LinkedIn. But for this past years, Instagram can take market attention. Due to a number of followers, culinary became favorite on Instagram. Before that, culinary products rarely marketed on other social media including Facebook. In this study, research will be focused on the kind of food that can be delivered in Semarang. This research will be started by sharing questionnaires to 157 respondents. Those respondents already have experience in buying food from Instagram in Semarang. From the result, two hypotheses accepted. The first one concluded there is a positive impact from brand reputation to buying decision. The second one concluded there is a positive impact on brand admiration to brand reputation. For reliability and product price didn’t give impact for buying decision.